Costa Rican test: Evaluation of the children’s integral development from 0 months to 6 years of age (EDIN II) - Quezada Ugalde, Ana María (2019)
The child development evaluation test for children between 0 months and 6 years (EDIN II) is an updated version of the Costa Rican EDIN development screening test. The objective was to analyze the EDIN II test, to continue to implement and screen the integral development of girls and boys. It was a descriptive quantitative-qualitative study. Data were collected through the expert judgment technique and the application of the test to a sample of 380 children. The main results obtained concerning the test were: classification according to the semaphore system, inclusion of a new age group of 12 to 15 months and 15 to 18 months, incorporation of the corrected age for under 2 years old children, and separation of the neurological assessment. On the other hand, the specific changes required by the items for which it was necessary to eliminate, make changes in the form and also the creation of new ones that contemplated development milestones, leaving 287 items in 5 areas of development and 20 groups old. For the instructive, it was necessary to specify better the execution of the items and to include expected answers that were not contemplated. And finally, some materials merited being replaced by others with better characteristics to evaluate the behaviors. It concluded to submit the test to subsequent validation processes so it can be included in the public policies for children.